Oxidative Stress and Antioxidants in Pediatric Asthma's Evolution and Management - Ileana Katerina Ioniuc; Ancuta Lupu; Felicia Dragan; Irina Tarnita; Monica Mihaela Alexoae; Violeta Streanga; Costica Mitrofan; Aye Aung Thet; Alin Horatiu Nedelcu; Delia Lidia Salaru; Stefan Lucian Burlea; Elena Cristina Mitrofan; et al. (MDPI AG, 2024)
Within the pediatric population, bronchial asthma is one of the most prevalent chronic respiratory system diseases. The number of exacerbations, severity, and duration of symptoms all have a significant impact on children's life quality. In the last decades, the prevention and management strategies of this pathology have focused on maintaining or even increasing the pulmonary function to maximum levels in early childhood, as it has been demonstrated that functional deficits at this level occurring before school age cause pathological manifestations later, in adulthood. The epithelium of the airways and implicitly that of the lung is the first barrier against the lesions caused by pro-oxidative factors. Both oxidative and antioxidative factors can be of endogenous origin (produced by the body) or exogenous (from the environment or diet). Good functioning of antioxidant defense mechanisms from the molecular level to the tissue level, and a balance between pro-oxidative factors and anti- oxidative factors, influence the occurrence of compensatory mechanisms at the level of the respiratory epithelium, causing the delay of local responses to the stress induced by chronic inflammation (bronchial remodeling, thickening of airway smooth muscles, bronchoconstriction, bronchial hyper-reactivity). These mechanisms underlie the pathophysiological changes in asthma. Numerous studies carried out among the pediatric population inclusively have demonstrated the effectiveness of antioxidants in the prophylaxis, slowing down and preventing the progression of this pathology. This review complements the scientific articles, aiming at emphasizing the complexity of oxidative physio-pathological pathways and their importance in the occurrence, development, and therapeutic response in asthma, providing a good understanding of the relationship between oxidative and antioxidative factors, and being a source of future therapeutic strategies.